Cultural Permanence for Indigenous Children and Youth: Reflections from a Delegated Aboriginal Agency in British Columbia - Bennett, Kathleen (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
The article discusses cultural permanence for Indigenous children and youth from the perspective of the executive director of Northwest Inter-Nation Family and Community Services (NIFCS), a delegated Aboriginal child welfare agency that serves nine Indigenous communities from three First Nations on British Columbia’s northwest coast. Through increasing cultural knowledge, NIFCS aims to enhance its practice to meet the holistic needs of children and youth in care, in particular, to ensure that children and youth maintain connections with their families, extended families, and communities. NIFCS provides experiential opportunities for children and youth to know about, and learn their languages, spiritual teachings, and cultural traditions from their Elders, families, and communities. Ultimately, NIFCS’s goal is for the children and youth in its care to be strongly connected to their roots and experience a sense of belonging. This paper looks at connectedness and cultural diversity in the context of cultural planning for permanence, relates these concepts to NIFCS, and outlines promising practices within NIFCS.